Autologous hematopoietic stem cell transplantation in chronic lymphocytic leukemia: results of European intergroup randomized trial comparing autografting versus observation - Michallet, Mauricette; Dreger, Peter; Sutton, Laurent; Brand, Ronald; Richards, Sue; van Os, Marleen; Sobh, Mohamad; Choquet, Sylvain; Corront, Bernadette; Dearden, Claire; Gratwohl, Alois; Herr, Wolfgang; et al. (Blood, 2011)
We present results of a phase 3 randomized trial of autografting in chronic lymphocytic leukemia versus observation for responding patients after first- or second-line treatment. The primary objective was to demonstrate that autografting improves the 5-year event-free survival (EFS) from 30% to 50%. There were 223 enrolled patients, 72% men and 28% women, 83% after first and 17% after second-line treatment. Binet stages were progressive A 13%, B 67%, C 20%; at randomization, 59% were in complete remission, and 41% in less than complete remission. Patients were randomized between autografting (n = 112) and observation (n = 111). Median EFS was 24.4 months (range, 16.7-32 months) in the observation group and 51.2 months (39.8-62.5 months) in the autografting group; the 5-year EFS was 24% and 42%, respectively (P < .001). Accordingly, the 5-year relapse incidence was 76% versus 54% (P < .001). Median time to relapse requiring therapy or death was 40 months (25-56 months) in the observation arm and 65 months (59-71 months) after autografting (P = .002). Cox modeling confirmed that autografting significantly improved EFS (hazard ratio 0.44, 95% confidence interval 0.30-0.65; P < .001). At 5 years, the probability of OS was 85.5% and 84.3% for autografting and observation, respectively (P = .77). In chronic lymphocytic leukemia, consolidating autografting reduces the risk of progression by more than 50% but has no effect on overall survival.